Desenvolvimento de metodologia para estimativa de velocidade do escoamento e do transporte de sedimentos em um escoamento raso - Coelho, Rogério Magalhães (2024)
Surface runoff corresponds to the segment of the hydrological cycle related to the movement of water over the soil surface. When runoff occurs in impermeable urban areas, it usually happens in shallow water depth, referred to as shallow flow. Characterizing shallow flow is challenging due to the impracticality of using conventional techniques, as they substantially alter the flow conditions themselves. During this phase, water pollution entering the stormwater collection system is typically more concentrated compared to the rest of the rainfall. Studies on rainfall-runoff behavior and material transport in rainfall and runoff simulators have increased due to the difficulty of data collection in urban environments and their greater ease, cost reduction, speeding up, and optimizing data collection. An alternative to traditional techniques for measuring sediment transport velocity by surface runoff in the simulator is infrared thermography, which is based on the physical phenomenon that every object, with a temperature above absolute zero (-273.15°C), emits electromagnetic radiation originating from the excitation of its constituent molecules. The methodology developed in this study used a thermal camera to analyze sediment transport velocity through the acquisition and processing of thermographic images, observing displacement, knowing the time interval, and using image processing software called Tracker, the sediment transport velocity could be determined under varied conditions and parameters. Experiments were conducted varying the flow rate and sediment granulometry, collecting optical and thermal data, in addition to using different techniques for determining velocity and flow and sediment transport. All techniques used were compared to each other to conclude which technique was the most representative. The optical measurement technique was less accurate regarding variations than the thermographic technique.